The Mediating effect of interpersonal influence between mass media nfluence and University Student’s Voting Intention - Wok, Saodah; Syed Abdullah Idid, Syed Arabi; Moten, Abdul Rashid (2012)
The role of media and the mediating influence of interpersonal communication has been a major concern in election studies; especially with regard to the voting intention of youth. The audience derives their knowledge of current news and political information from the mass media, which could be the starting point for interpersonal discussion. As such, this study investigates the relationships between media influence and the mediating effect of interpersonal influence on voting intention of university students in Malaysia. The study applies the limited theory and the agenda setting theory to test the existence of the interpersonal influence in voting intention in mediating the media influence. Data were collected from 9036 undergraduate students from 20 IPTA and 8 IPTS; using questionnaire as the research instrument from March through May 2011. Data were analyzed using SPSS Win 16 for both descriptive and inferential statistics. The respondents were mainly female, Malays, from all states in Malaysia. They surf the Internet every day while were less exposed to the traditional media. They are more interested in the current news than the political news. But, it is difficult to differentiate between current and political news. The testing of the mediating effect of the interpersonal media is applicable for BN student supporters than the for the BA student supporters. Therefore, the limited theory and the agenda setting hold true for BN potential voters only. More has be studied and learned from BA potential student voters.